Structural effects of the Solanum steroids solasodine, diosgenin and solanine on human erythrocytes and molecular models of eukaryotic membranes (2014)
ABSTRACT: This report presents evidence that the following Solanum steroids: solasodine, diosgenin and solanine interact with human erythrocytes and molecular models of their membranes as follows: a) X-ray diffraction studies showed that the compounds at low molar ratios (0.1–10.0 mol%) induced increasing structural perturbation to dimyristoylphosphatidylcholine bilayers and to a considerable lower extent to those of dimyristoylphosphatidylethanolamine; b) differential scanning calorimetry data showed that the compounds were able to alter the cooperativity of dimyristoylphosphatidylcholine, dimyristoylphosphatidylethanolamine and dimyristoylphosphatidylserine phase transitions in a concentration-dependent manner; c) in the presence of steroids, the fluorescence of Merocyanine 540 incorporated to the membranes decreased suggesting a fluidization of the lipid system; d) scanning electron microscopy observations showed that all steroids altered the normal shape of human erythrocytes inducing mainly echinocytosis, characterized by the formation of blebs in their surfaces, an indication that their molecules are located into the outer monolayer of the erythrocyte membrane.